1994
DOI: 10.1159/000139179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prostacyclin and Beraprost on Ciliary Motilitγ of Rabbit Airway Epithelium

Abstract: The effects of prostacyclin and its stable analog beraprost on ciliary beat frequency (CBF) of rabbit tracheal epithelium were studied by a microphoto-oscillation technique in vitro. Addition of these drugs increased CBF in a dose-dependent fashion: the maximal increase from the baseline value and the drug concentration required to produce a half-maximal effect were 13.3 ± 2.0% (p < 0.05) and 1.8 ± 0.4 × 10-7 mol/l for prostacyclin and 30.8 ± 3.4% (p < 0.001) and 1.6 ± 0.5 × 10-7 mol/l fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For example, some authors have found that erythromycin inhibits the chemotaxis of PMNs, while others have found that it does not. 9,19 These differences may be explained, in part, by technical differences, as some tests were carried out in animals, 19 some used cells harvested from animals treated with the macrolide (ex vivo) 12,14 and some were conducted purely in vitro. 20 In addition, the mechanism by which conventional anti-inflammatory drugs work is complex and not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some authors have found that erythromycin inhibits the chemotaxis of PMNs, while others have found that it does not. 9,19 These differences may be explained, in part, by technical differences, as some tests were carried out in animals, 19 some used cells harvested from animals treated with the macrolide (ex vivo) 12,14 and some were conducted purely in vitro. 20 In addition, the mechanism by which conventional anti-inflammatory drugs work is complex and not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations have shown that PGE2 acts through cAMP and NO second messengers in rat liver macrophages, 20 and that PGI2 analogs can stimulate ciliary activity via endogenous cAMP production. 21 At higher concentrations, methacholine could stimulate the cyclooxygenase pathway, producing prostaglandins. These endogenous prostaglandins could regulate CBF via stimulation of cAMP production.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the increase of cilia motility may be achieved by application of prostacyclin [37], a neuromodulatory peptide -substance P (SP) [38], or methacholine, a non-selective agonist of cholinergic (muscarinic) receptors [39]. Also, it has been proven that cilia beats frequency may increase following the activation of adrenergic and purinergic receptors [15,40].…”
Section: "Modifiers" Of Cilia Movementmentioning
confidence: 99%